Effect of Mn on Fe containing phase formation in high purity aluminium. (August 2014) - Yan, F.; Kumar, S.; McKay, B. J.; O'Reilly, K. A. Q.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, the effect of varying Mn additions on Fe phase formation in high purity Al and its corresponding effect on the resulting mechanical properties have been investigated. Thermodynamic simulations have shown that in the Al–Fe–Mn ternary system two intermetallic phases (namely Al6(Fe, Mn) and Al13Fe4) form. Findings indicated that a relatively high amount (>1 wt-%) of Mn was required to achieve Al6(FeMn) phase formation which was congruent with experimental results. Both the Al–Fe and Al–Fe–Mn phases observed displayed fibre/platelet type morphologies and were found to exist at α-Al grain/cell boundaries. Results indicate that the Fe phases coarsen with increasing Mn content. In the Al–Fe system the Mn addition improves yield strength (YS) and ultimate tensile strength (UTS) but reduces elongation beyond the reduction resulting from the Fe addition. The further decrease in elongation with Mn was attributed to the increase in volume fraction of the intermetallic phases.